Análisis y mejora en el proceso de producción de Andreatex S.A.C. utilizando la herramienta mantenimiento productivo total del Lean Manufacturing - Lopez Olmos, Isaac Edwin (2022)
This research is carried out in the production process of a clothing company dedicated to the manufacture and marketing of merchandising articles, with the objective of reducing the variability in the process using Lean tools. By performing an analysis of the current situation of the company, the production process is selected as the most critical. In the definition stage, the main problem that turns out to be the breach in the delivery time of T-shirt orders is identified. Therefore, it is necessary to describe the process and identify the client's voice in order to develop a Lean project. In the measurement stage, the variable to be measured is identified, which is the production time in days, with the orders for poles classified as medium being those with the greatest economic impact. Performing the calculation of the potential and real capacity of the process and a study of the XR control charts and the attribute type. In the analysis stage, the root causes of the problem are determined and analyzed, these being the ones that directly affect customer satisfaction using the Ishikawa diagram For the selection of the solution proposal, two alternatives were proposed, confronting them with 4 evaluation criteria, the one chosen being the application of a total productive maintenance (TPM) according to the Lean Manufacturing guidelines. In the improvement stage, the implementation of the TPM in the production area is established; In the first instance, the calculation of the overall effectiveness of the equipment (OEE) is performed, having a value of 64%, therefore, the implementation of the 5's is carried out to improve the effectiveness of the equipment. Finally, a NPV of S/ 12 658,69 and an economic IRR of 41,24% with an investment of S/ 12 000 concluding that the project is economically viable.